HOLOGRAPHY AND VIRTUAL REALITY IN THE TEACHING OF NANOTECHNOLOGY: NEW HORIZONS AIMED AT HIGH SCHOOL - Ribeiro, Allan V.; Godoy, Gabriela C.; Neto, Luiz Belini; Souza-Filho, Moacir P. de [UNESP] (Univ Nacl Colombia, Fac Sci, 2018)
Use almost inseparable from the technological resources in social, professional and emotional dimensions, suggest a new process of sociocultural and cognitive resignification. Such developments gain notoriety with the advent of new technologies of information and communication (NTIC), bringing new horizons for educational practices. ICTs in the future will be based on emerging technologies that will integrate and articulate knowledge from different areas of knowledge in an interdisciplinary manner in educational proposals. These disruptive technologies tend to provide significant advances in areas such as: technology information, holography, nanotechnology, biotechnology, cognitive science, robotics and artificial intelligence. Among this range of possibilities, including technologies capable of express representations of reality or imagination, sometimes difficult to abstraction. In this context, holography and virtual reality meet methodological assumptions that act in an active way and that motivate, with high power of illustration and interactivity. This paper presents the findings on the use of holography and virtual reality for the teaching of concepts in nanoscience and nanotechnology (N&N) in secondary education. Methodologically, this work was developed with use of these technologies for the teaching of N&N in scientific events in the period between 2015 and 2017. The results show that the interactive elements of these technologies can enhance and corroborate to the meaningful learning of concepts related to N&N, and which are difficult for the abstraction of the students.
Keywords: Emerging technologies; virtual reality; holography; NTICs